Analisis Sensitivitas Metode AHP Dan TOPSIS Dalam Pemilihan Objek Wisata di Kabupaten Karangasem - I Gede Iwan Sudipa; I Kadek Hardiatama; Christina Purnama Yanti; I Komang Arya Ganda Wiguna (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Bali is a well-known tourist destination, but Karangasem is not widely known to the public. Tourist objects are selected as Multi-Attribute Decision Making (MADM). This study analyzes the MADM problem, namely the selection of tourist objects using the Analytical Hierarchy Process (AHP) and The Technique for Order Preferences by Similarity to an Ideal Solution (TOPSIS) method. Method testing is done by conducting a sensitivity analysis to determine the most sensitive method in selecting tourist objects. The sensitivity analysis on 10 trials by changing the weight of the criteria by adding values ​​from 1 to 2 shows that the AHP method produces a ranking change of 440 with a percentage of 5.6%. While the TOPSIS method has a ranking change of 292 with a percentage of 3.77%. The results show that the AHP method is more sensitive to changes in weight, so relevant decision-making in selecting Karangasem Regency tourism objects can be carried out using the AHP method.